Implementation of Policy Regulation of the Minister of Maritime Affairs and Fisheries Number 17 of 2019 Regarding the Processing and Marketing of Marine and Fishery Products Quality Development Section: Strategy of the East Java Province Maritime and Fisheries Service in Improving the Quality of Fishery Product Processing - Annisa Ayu Sholihah; Vidya Imanuari Pertiwi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This research discusses the implementation of the policy of Minister of Maritime Affairs and Fisheries Regulation Number 17 of 2019 regarding the Processing and Marketing of Marine and Fishery Products (P3KP) by the Quality Development Section at the East Java Province Maritime and Fisheries Service (DKP). Using a descriptive qualitative approach and Van Meter and Van Horn's policy implementation theory, this research analyzes P3KP strategies in improving the quality of processing and marketing of fishery products. The results of the research show that the success of implementing this policy is influenced by six factors which include, policy standards and targets, resources, characteristics of implementing organizations, attitudes or responses of implementers, communication between related organizations and implementation activities, as well as social, economic and social conditions. political. Some of the main programs in this implementation include product monitoring, providing assistance with infrastructure, and facilitating certification for fisheries business actors. It is hoped that this study can provide strategic recommendations for the development of the fisheries sector and increase public awareness of the importance of ensuring the quality of marine and fishery products.